A arte de recomeçar: uma compreensão da dinâmica das famílias recasadas - Costa, Juliana Monteiro (2008)
The present study had the purpose to investigate how one of the members of the remarried couple, for at least two years, leaves this experience. The complexity and diversity presents in the remarried family structure, as well as the constant increase of this familiar configuration, indicates that the model o a nuclear family to which the remarried families are compared it is not an adequate parameter. Consulted literature stands out that the essential differences between these formats of family must be considered by the diverse professionals who work with the new familiar configurations. A field research was made based on a literature review in which eight people who inhabited in the city of Recife. The group of interviewed was constituted by five people of the feminine sex and three of the masculine sex, all remarried and with children of previous marriage, either biological or adoptive. From the theoretical recital and of the speech of the participants, seven categories of analysis had been proposed. The evaluation of the gotten material sample that the interviewed ones deal with the remarriage as an union of steady character, where they share not only the residence, but all the pertinent activities to a couple, in a recognized marriage for law. All the participants had been unanimous in affirming that the four first years of contact are sufficiently delicate, demanding of the couple biggest flexibility, attention and care so that a familiar integration occurs. We observe, also, a certain difficulty between the members of this family how to the exercitate each ones function